Analisis Dampak Kebijakan Alokasi Anggaran untuk Sektor Pariwisata terhadap Kelompok Masyarakat Pariwisata Berkelanjutan di Destinasi Wisata Situ Cileunca Kabupaten Bandung - Ramdani, Dadan (Al-DYAS, 2025)
The need to evaluate the extent to which public budget policies impact the empowerment of community groups in sustainable tourism serves as the background for this study, particularly in the Situ Cileunca area of Bandung Regency, which is experiencing growth as a nature-based tourism destination. The objective of this research is to understand the impact of budget allocation policies in the tourism sector on surrounding communities in social, economic, and environmental aspects. Employing a descriptive qualitative approach, data were collected through direct observation and interviews with tourists, local MSME actors/vendors, and non-managing residents. The findings indicate that regional government budget policies have had a positive impact on the development of public facilities and community empowerment, although support remains uneven, especially in the provision of information boards and waste management systems. MSME actors reported increased income due to the rise in tourist visits; however, most have yet to receive training, outreach, or direct assistance from the government. These findings underscore the need for more responsive budget policies that comprehensively prioritize local community empowerment. The implications of this study include contributions to the literature on sustainable tourism and policy recommendations for tourism development that is more inclusive, adaptive, and socially just.